(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Urinary tract infections (UTIs) are among the most common bacterial infections in children, and rising antimicrobial resistance has prompted interest in plant-based therapeutic alternatives. Objective: To evaluate the antimicrobial potential of selected medicinal plants against uropathogens isolated from pediatric UTI patients. Methodology: This experimental laboratory-based study was conducted at the Department of Pharmacology, University of Balochistan, Quetta, using urine samples collected from pediatric patients (aged 1–14 years) with culture-confirmed UTIs at the Sheikh Khalifa Bin Zayed Hospital, Quetta. A total of 160 non-duplicate bacterial isolates were obtained. Standard microbiological methods were used for pathogen identification, and plant extracts [Azadirachta indica (Neem), Ocimum sanctum (Tulsi), Zingiber officinale (Ginger), Nigella sativa (Black Seed)] were prepared and tested. Phytochemical screening was performed, and antimicrobial activity was assessed using agar well diffusion, MIC, and MBC assays, with comparisons made against standard antibiotics following CLSI guidelines. Results: Among 160 pediatric UTI isolates, Escherichia coli was the predominant pathogen (61.25%), followed by Klebsiella pneumoniae (17.50%) and Proteus mirabilis (8.75%). Phytochemical screening revealed the presence of alkaloids, flavonoids, tannins, saponins, and phenolics in most extracts. Ocimum sanctum (Tulsi) exhibited the highest antimicrobial activity with inhibition zones of 15.6 ± 1.4 mm against E. coli and 14.1 ± 1.3 mm against Klebsiella pneumoniae, followed by Nigella sativa (Black seed) with 14.3 ± 1.2 mm. Minimum inhibitory concentration (MIC) values for Tulsi ranged from 100–130 µg/mL, while Nigella sativa showed 150–200 µg/mL. Both extracts outperformed ampicillin (10.9–12.3 mm) but were slightly less effective than nitrofurantoin (15.6–18.5 mm) and ciprofloxacin (18.9–22.3 mm) Conclusion: Medicinal plants, particularly Tulsi and Black seed, show promising antimicrobial activity and may serve as adjunct or alternative therapies in pediatric UTI management.